2022
DOI: 10.4103/picr.picr_202_19
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of the World Health Organization access, watch reserve index to evaluate and monitor the use of antibiotics at a tertiary care hospital in India

Abstract: Background: The World Health Organization classification of antibiotics classifies key antibiotics into access, watch, and reserve (AWaRe) categories. Categorization provides a novel metrics called “AWaRe index” to study and monitor antibiotic consumption globally and within the same setting over time. Aim: The aim of this study is to compare the use of antibiotics in 2 years using the AWaRe index tool. Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…The overall prescribing of antibiotics in our study is lower than the WHO recommendations, which state that more than 60% of all prescribed antibiotics must be from the Access group by 2023. Figures in our study are consistent with another Indian study which had Access (53.31%), Watch (40.09%) from, and Reserve (3.40%) category[ 16 ], and study done in Zambia with ( n = 384) which had Access (55.5%), Watch (43.1%) and Reserve (1.4%)[ 7 ]. Our findings differ from another study in India[ 17 ] in which Watch group antibiotics accounted for 53.19 % of the total antibiotics and a Bangladesh study in which 64.0% of the patients were treated with antibiotics from the Watch group, 35.6% were treated with antibiotics from the Access group, and only 0.1% were treated with antibiotics from the Reserve group.…”
Section: Discussionsupporting
confidence: 92%
“…The overall prescribing of antibiotics in our study is lower than the WHO recommendations, which state that more than 60% of all prescribed antibiotics must be from the Access group by 2023. Figures in our study are consistent with another Indian study which had Access (53.31%), Watch (40.09%) from, and Reserve (3.40%) category[ 16 ], and study done in Zambia with ( n = 384) which had Access (55.5%), Watch (43.1%) and Reserve (1.4%)[ 7 ]. Our findings differ from another study in India[ 17 ] in which Watch group antibiotics accounted for 53.19 % of the total antibiotics and a Bangladesh study in which 64.0% of the patients were treated with antibiotics from the Watch group, 35.6% were treated with antibiotics from the Access group, and only 0.1% were treated with antibiotics from the Reserve group.…”
Section: Discussionsupporting
confidence: 92%
“…Studies from different regions of India shows that penicillins and cephalosporins are being interchangeably used as the most commonly prescribed antibiotics. [ 19 20 21 22 23 27 ] The consistency of our results with previous studies suggests that patterns of use of different classes of antibiotics have changed little over time.…”
Section: Discussionsupporting
confidence: 86%
“…The study showed that, in 2017, 53.31% of antibiotics prescribed belonged to Access, 40.09% to watch and 3.40% to reserve category respectively as compared to 41.21%, 46.94% and 8.15% respectively in 2018. [ 21 ] Though the WHO AWaRe classification specified that at least 60% of antibiotics should be prescribed from the Access group, Hsia et al . in their Point Prevalance Survey (PPS survey, included patients from 56 countries) observed high diversity in patterns of AWaRe antibiotic use among countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This upward trend in azithromycin usage aligns with findings from a variety of international research efforts. In India, studies by Mugada et al (2021) and Sharma et al (2021) reported similar patterns, reflecting a broader shift in antibiotic prescription practices. In Malaysia, Mohamad et al (2022) also observed an increase.…”
Section: Discussionmentioning
confidence: 76%